HUBUNGAN PENGETAHUAN DAN MOTIVASI IBU DENGAN PEMBERIAN MP-ASI DI WILAYAH KERJA PUSKESMAS RAWASARI KOTA JAMBI - Iin Indrawati; Putri Qoriah Anggini (Jurnal Akademika Baiturrahim Jambi, 2018)
Prevalence of malnutrition in Indonesia 2013, consists of 5.7% and 13.9% malnutrition. Giving breast milk too early may have a negative impact on the health of the baby. In infants who have missed the MP-ASI will lead to malnutrition. This research was conducted using the analytical method. The research was conducted in 2-14 September 2016. The population in this study were mothers of infants aged 6-11 months in Puskesmas Rawasari Jambi City in Agust 2016 that is 73 babies. The research sample is taken by simple random sampling technique totaling 42 babies. Collecting data in this study using a questionnaire measuring instrument with a questionnaire. The analysis used were univariate and bivariate. The results showed that most respondents had a good knowledge of 30 respondents (71%), less well motivated as many as 25 respondents (40%) and have good behavior, namely 23 respondents (55%). The analysis showed that there is not a relationship between the mother's knowledge with the mother’s habit of giving breast milk p value 0,192.and motivationshowed that there is a relationship with the mother's habit of giving breast milk p value 0,008 in that region Rawasari Work Puskesmas Kota Jambi.And alpha value 0.005.